GEREJA UNIVERSAL DAN FASILITAS RETRET DENGAN PENDEKATAN METAFISIKA DI BANDUNGAN - Ginda Chriesma Yoga; Widi Suroto; Hardiyati Hardiyati (ARSITEKTURA, 2016)
This time, in the modern era, human lifestyle are increasingly changing the human habit who makes them more concern with a worldly life and tarnished their needs of God, thus starving of their spirit has been ignored. For some people to go to church only be regarded as a formality or just things that do not even need to do. This makes human have lack understanding about the human essence which are part of God creation. Now, the church only seen as a building which is place to worship, the true meaning from the church is the human itself. This deconstruction of meaning are writer try to reverse back as a basis of Church planning and design. The problem in this design process is how to design church which can make physical and psychological impact to the user. The Universal Church of Metaphysics approach is most suitable appointed because the elements of Metaphysics Architecture can give impact to user psychical and physical. The Universal means intended to accommodate all of the Nazarenes, not only for Christian or Catholic believes, as well as to facilitate all people physical condition, normal people or disabilities people. Metaphysics Architecture can be achieved from some aspects consist of archetype, nature, light, materials, human, and memories which will be creating particular feel and atmosphere in the design. The main target of this architecture form is the user that is human. All of senses and sensors on the human body become essence in this work. Through planning location, nature, and all of architectural details which writer implemented to Universal Church and Retreat Facilities design, which have an aim to restore the human essence and can ‘presenting’ the God inside of the design. Keywords: Human and God, Metaphysics Phenomenon, Universal Church